A Prospective Evaluation of Adverse Reactions to Single-Dose Intravenous Antibiotic Prophylaxis During Outpatient Hand Surgery. (January 2020) - Sandrowski, Kristin; Edelman, David; Rivlin, Michael; Jones, Christopher; Wang, Mark; Gallant, Gregory; Beredjiklian, Pedro K.
Background: While it is established that routine prophylactic antibiotics are not needed for all hand surgery, some cases do require it. The purpose of this study was to determine the rate of adverse reactions resulting from prophylactic antibiotic administration on patients undergoing outpatient hand and upper extremity surgical procedures. We hypothesize that the rate of complications resulting from the use of antibiotic prophylaxis is smaller than that reported in the currently referenced literature.Methods: We prospectively evaluated 570 consecutive patients undergoing outpatient upper extremity surgery. Patients were excluded if they were on antibiotics prior to surgery, were discharged on antibiotics, or if they wished to be excluded. Nineteen patients were excluded, resulting in a study cohort of 551 patients. Patients were monitored perioperatively, 2 to 3 days postoperatively, during the first postoperative visit and 1 month postoperatively for adverse reactions. The type and timing of the adverse reaction was recorded.Results: Five hundred fifty-one patients were included for evaluation and 8 patients (1.5%) developed an adverse reaction to antibiotics. Five patients (0.9%) reported a rash and 3 patients (0.5%) reported diarrhea within 3 days of surgery. There were no anaphylactic reactions or complications necessitating hospital transfer or admission in the postoperative period.Conclusion: This study represents a prospective investigation designed to determine the rate of adverse reactions to single-dose antibiotics given during outpatient hand surgery. We conclude that the use of intravenous, single-dose prophylactic antibiotic is safe in the outpatient setting for cases that require it.